Application of spectral analysis of surface waves (SASW) method: rock mass characterization - Goh .T.L; Abdul Rahim Samsudin; Abdul Ghani Rafek (Universiti Kebangsaan Malaysia, 2011)
A geotechnical study needs to be carried out to determine the engineering parameters of the rock mass at the project site in executing construction projects such as tunnels, dams, highways and buildings. Design and safety factor of the construction are highly dependent on soil and rock engineering parameters which are usually determined by in-situ test such as Standard Penetration Test (SPT) and seismic tests. The SPT test which normally involves drilling and laboratory works always incur high operating cost, while seismic tests on the other hand are fast, cheap, non-destructive and an easy to operate method for rock mass characterization. The spectral analysis of surface waves (SASW) method is an in situ and non-destructive measurement that is rapid and cost effective. The aims of this study were to determine Rock Quality Designation (RQD) value, excavation classification analysis as well as site characterization by using the SASW method. WinSASW 3.1.3 was used for inversion processing of the SASW data to produce shear wave velocity (Vs) versus depth profiles. The profiles were then analyzed and correlated with rock mass engineering geological parameters such as RQD and site characterization as well as excavation classification of rock mass. Twenty (20) SASW tests were conducted on the granitic rock mass and four (4) SASW tests were conducted on a cut hill slope of metasedimentary rocks. RQD values were computed based on shear wave velocities and ultrasonic velocities of intact (fresh) rock. The differences between RQD obtained from SASW method and those from discontinuity survey were found to be less than 10%. Excavation classification for granitic rock mass at JKR Quarry was empirically determined using both SASW and ultrasonic velocities as well as RQD value of the rock mass. Site characterization for metasedimentary rocks mass at Bukit Tampoi was determined based on shear wave velocities from SASW method.